Biomimetics with nanofibre meshes - Martins, Albino (2012)
Bone is a complex and a highly specialised form of connective tissue defining the structure and shape of the skeletal system. Bone, not only provides mechanical support but also serves as an elegant reservoir for minerals, particularly calcium and phosphate [1]. Structurally, bone is an amazing nanostructured composite material comprising two major phases: an organic matrix phase, mainly composed of proteins (such as collagen and proteoglycans), and an inorganic phase that consists of crystalline calcium hydroxyapatite (HAp) deposited within the nanofibrous matrix surface. The collagen in bone (type I) has a typical fibrous structure, whose diameter varies from 100 to 2000 nm. The mineral phase is in the form of HAp nanocrystals that are deposited at the surface of the collagen fibrils, with spacing dimensions of about 4 nm by 50 nm spacing. At the submicron level, this organic-inorganic combination confers the intrinsic and unique biomechanical and functional properties that assemble into the three-dimensional (3D) bone architecture. While the proteins mediate the functions of the bone cells such as promoting, inhibiting, or regulating bone synthesis and resorption, the HAp crystals confer the stiffness of bone. Indeed, it is believed that the key element in defining the unusual strength of bone is the complex structural hierarchy into which it is organised in a self-assembly mode [1]. Synthetic polymers typically allow greater ability to tailor a wide range of properties, are more homogeneous and allow easier processing. Nevertheless, synthetic polymers lack bioactivity properties to stimulate biological functions, such as cell affinity, bioactivity, or osteoconductivity. Concerning these properties, ceramic materials may have some advantage for scaffold fabrication, despite their limited mechanical properties, as bone fillers or as matrices for bone repair strategies. Although there is good progress in bone grafting using synthetic bone grafts, the way in which they execute their function in vivo is quite different from natural bone both compositionally and structurally [1]. There is, therefore, a great need for engineering multi-phase materials (so-called composites) with structure and composition similar to natural bone. Recently, nanocomposites, particularly HAp- and collagen-based, have gained much recognition as bone grafts, not only because of their composition and structural similarity with natural bone, but also because of their unique functional properties such as larger surface area and superior mechanical strength than their single-phase constituents. The use of nanotechnology to tailor scaffolds for orthopaedic applications arises from the recognised advantage in mimicking the ECM structure and complexity at the biological level. Consequently, an increasing interest has been devoted to the polymer processing technique called electrospinning. This technology results in the production of biocompatible micro- and nano-structured scaffolds made of an ultra- fine and continuous fibre network with variable pore-size distribution, high micro- porosity and high surface-to-volume ratio, morphologically similar to the natural ECM [2]. Several materials including synthetic- and natural-origin polymers [3-9] and proteins [3, 4, 10], have been successfully electrospun into nanofibre scaffolds. Those structures were shown to interact positively with intercellular communications by sustaining cell adhesion, proliferation and differentiation towards the osteogenic phenotype both in vitro [3, 5, 7, 9] and in vivo [3, 5, 8]. The previously described properties together with the flexibility in allowing the incorporation of biologically active factors, such as matrix proteins [11], calcium phosphates [5, 6, 12, 13], either in the as-spun fibres or as coatings, makes these systems attractive for improving scaffold designs for bone applications. A novel way of fabricating nanocomposite bone grafts using strategies found in nature has recently received much attention and is perceived to be beneficial over conventional methods. Several attempts were made at investigating biomimetic processes. Biomimetic processes are defined as the ones that either mimic or are inspired by biological mechanisms, to incorporate desirable nano-features that emulate nature’s own structures or functions, aiming to develop the next generation bone grafts. Nanostructured biomaterials, having less than 100 nm in at least one dimension, in particular nanocomposites, are perceived to be beneficial and potentially adequate for bone applications, because of their nanoscale functional characteristics that facilitate bone cell growth and subsequent tissue formation [14]. All these attempts are thoroughly analysed in this chapter.